Wide trail strategy without separable codes - Rodinko, M. Yu.; Lisitskiy, K. E. (ХНУРЭ, 2015)
Implementation of the wide trail strategy within a single transformation without separation into linear and nonlinear parts is proposed. This possibility consists in the procedure of a consistent activation of Sboxes of the round function one by one by using managed substitutions. It is shown that the proposed transformation is completely identical to the original transformation of Rijndael on its differential and linear properties. The proposed construction allows obtaining maximum branch number. It means that one S-box input activates the subsequent S-boxes of transformation.
Keywords: round function; original transformation of Rijndael